Ferroelectric and optical properties of Ba0.8Sr0.2TiO3 thin film - Pontes, F. M.; Leite, E. R.; Pontes, DSL; Longo, Elson [UNESP]; Santos, EMS; Mergulhao, S.; Pizani, P. S.; Lanciotti, F.; Boschi, T. M.; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2002)
Barium strontium titanate (Ba0.8Sr0.2TiO3) thin films have been prepared on Pt/Ti/SiO2/Si substrates using a soft solution processing. X-ray diffraction and also micro-Raman spectroscopy showed that the Ba0.8Sr0.2TiO3 thin films exhibited a tetragonal structure at room temperature. The presence of Raman active modes was clearly shown at the 299 and 725 cm(-1) peaks. The tetragonal-to-cubic phase transition in the Ba0.8Sr0.2TiO3 thin films is broadened, and suppressed at about 35 degreesC, with a maximum dielectric constant of 948 (100 kHz). Electrical measurements for the prepared Ba0.8Sr0.2TiO3 thin films showed a remnant polarization (P-r) of 6.5 muC/cm(2), a coercive field (E-c) of 41 kV/cm, and good insulating properties. The dispersion of the refractive index is interpreted in terms of a single electronic oscillator at 6.97 eV. The direct band gap energy (E-g) and the refractive index (n) are estimated to be 3.3 eV and n = 2.27-2.10, respectively. (C) 2002 American Institute of Physics.